The Effectiveness of Webtoon to Develop Students' Writing Skill in Narrative Text Of Tenth Grader In SMK PGRI 13 Surabaya - Nova Ratnasari; Linda Mayasari; Sulton Dedi Wijaya (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2018)
There are four main skills in learning English, writing, listening, reading, and speaking. In this research, the researcher focused on writing narrative text for tenth grader students of SMK PGRI 13 Surabaya. The medium that is used in this research is webtoon. It is kind of comic series which has picture and narration so it can be make the students learn how to write narrative text easier. The purpose of this research is to find out the effectiveness of webtoon in developing students’ writing skill in narrative text. The researcher used quantitative method and the data were collected through pre-test, post-test, and questionnaire. The researcher used two classes, experimental class and control class to do this research. After the data were collected and calculated, the result showed that the average of score got an increasing. Before getting treatment, the average score of experimental class was 55 and after getting treatment, the average score was becoming 69. Furthermore, based on the students’ response, it showed that mostly the students agreed that webtoon is useful to use in learning English, especially writing skill so webtoon can be effective to develop students’ writing skill in narrative text.